2010
DOI: 10.1068/p6558
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Reduced Contrast on the Perception and Control of Speed When Driving

Abstract: Misperception of speed under low-contrast conditions has been identified as a possible contributor to motor vehicle crashes in fog. To test this hypothesis, we investigated the effects of reduced contrast on drivers' perception and control of speed while driving under real-world conditions. Fourteen participants drove around a 2.85 km closed road course under three visual conditions: clear view and with two levels of reduced contrast created by diffusing filters on the windscreen and side windows. Three depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 46 publications
(65 reference statements)
4
36
0
Order By: Relevance
“…Previous studies suggested that the speed of visual motion in depth is underestimated when the global level of contrast is reduced (Snowden et al, 1998; Horswill and Plooy, 2008; Owens et al, 2010). These studies were directly inspired by classical vision research experiments that assessed the effect of contrast on the perceived speed of two-dimensional objects on a monitor (Thompson, 1982; Stone and Thompson, 1992; Blakemore and Snowden, 1999; Anstis, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies suggested that the speed of visual motion in depth is underestimated when the global level of contrast is reduced (Snowden et al, 1998; Horswill and Plooy, 2008; Owens et al, 2010). These studies were directly inspired by classical vision research experiments that assessed the effect of contrast on the perceived speed of two-dimensional objects on a monitor (Thompson, 1982; Stone and Thompson, 1992; Blakemore and Snowden, 1999; Anstis, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…These studies have shown that the perceived speed of two-dimensional moving objects—for example, plaid patterns on a computer screen—is underestimated when visual contrast is reduced. More recent studies based on driving scenarios have suggested that the underestimation of visual speed at low contrast applies also to perceived self-motion in three-dimensional environments (Snowden et al, 1998; Horswill and Plooy, 2008; Owens et al, 2010). This finding was proposed—and is still considered—as a possible explanation for excessive driving speed in fog.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have suggested that drivers tend to underestimate their speed when driving under fog conditions. 1618 In foggy conditions, drivers may think they are driving more slowly than they actually are and, therefore, increase their speed. Due to their reduced field of view, speed misestimation could be even worse for glaucoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…15 Previous studies have suggested that drivers tend to underestimate their speed when driving in fog conditions and, thus, drive too fast for the available preview. 1618 This occurs because a reduction in optic flow and scene contrast suppress perception of speed under these adverse conditions. Since fog causes a reduction in contrast of the visual field, the apparent speed of the vehicle slows, causing the individuals to drive faster.…”
Section: Introductionmentioning
confidence: 99%